Prevalence and associated risk factors of cryptosporidiosis among cattle in the region of eastern Algeria (VETERINARIA, 2020)
A cross-sectional study was undertaken to determine the prevalence and assess the potential risk factors for Cryptosporidium spp infection among the calves in and around Annaba town, eastern Algeria in both traditional breeding farms and smallholders, and in cross and local calves breed. Three hundred and forty fecal samples were collected from the calves younger than four months, and screened for Cryptosporidium spp oocysts by microscopy. The overall prevalence rate was 24.11%. Associations between each independent variable including age, type of rearing room, hygienic condition of the calves and cryptosporidiosis infection were statistically significant (p
Keywords: Algeria; calves; Cryptosporidium spp; prevalence; risk factors